Immune Effects of Corticosteroids in Sepsis - Heming, Nicholas; Sivanandamoorthy, Sivanthiny; Meng, Paris; Bounab, Rania; Annane, Djillali (Frontiers in Immunology, 2018)
Sepsis, a life threatening organ dysfunction, results from a dysregulated host response to invading pathogens that may be characterized by overwhelming systemic inflammation or some sort of immune paralysis. Sepsis remains a major cause of morbidity and mortality. Treatment is nonspecific and relies on source control and organ support. Septic shock, the most severe form of sepsis is associated with the highest rate of mortality. Two large multicentre trials, undertaken 15 years apart, found that the combination of hydrocortisone and fludrocortisone significantly reduces mortality in septic shock. The corticosteroids family is composed by several molecules that are usually characterized according to their glucocorticoid and mineralocorticoid power, and their non-genomic effects relative to hydrocortisone. While the immune effects of glucocorticoids whether mediated or not by the intracellular glucocorticoid receptor have been investigated for several decades, it is only very recently that potential immune effects of mineralocorticoids via non-renal mineralocorticoid receptors have gained popularity. We reviewed the respective role of glucocorticoids and mineralocorticoids in counteracting sepsis associated dysregulated immune systems.